TREATMENT- A PERSPECTIVE IN SOCIAL WORK AND A CHALLENGE FOR SOCIAL WORKERS - Trajkov, Ivan (Ревија за социјална политика/Journal of Social Policy, 2015)
The field of social work in Macedonia was developed in several stages; in each of these there has been advancement in education and professional development of social workers. The role of a social worker in the past would be more in administration day, they are analysts and researchers who, coping with the modern day issues and the consequences of the social existence of the growing number of individuals and groups, are facing the challenges of using new modes of assistance and improving the mental and social state of users. Their line of work implies dealing with individuals and groups of various ages, with various problems (misconduct, substance abuse, post-violence effect, stress, mental illness), which, among others, are the result of the detrimental influence of the family and wider social setting, thus creating the need to use alternative therapeutic methods and techniques in reducing the negative social impact.